Improvement Welfare Farmer through Sustainable Land Management A Study of Economic and Environmental Outcomes in Agroecosystem - Junaedi, Ajeng Syadiar (Politeknik Siber Cerdika Internasional, 2024)
Changes climate and degradation ongoing land​ globally causing​ challenge significant for farmers , especially in increase productivity and maintaining sustainability environment . Management land sustainable become approach important For overcome problem said . Research This aiming For analyze impact implementation technique management land sustainable to welfare economy farmers and quality environment in the research area . Research This use method quantitative descriptive with sample as many as 100 farmers have apply technique like rotation plants , agroforestry , and use fertilizer organic . Data collected through survey , observation field , and interviews , then analyzed use statistics descriptive and multiple linear regression . The results of the study show that technique management land sustainable increase income farmer up to 25% and repair quality land and water conservation . On the other hand , the obstacles main implementation technique This covering lack of knowledge technical and cost high start . Research​ This give proof empirical that management land sustainable can increase welfare economy farmers and support effort conservation environment , so that worthy For pushed in policy agriculture national.